Гигантобивневые мастодонты Северного Причерноморья в пределах УССР - Короткевич, Е.Л. (Вестник зоологии, 1979)
Differences are marked in the skull and teeth of “grandincisivus” from the Late Miocene different-age deposits of Cherevichny and Novoukrainka (Odessa Region). These mastodons, perhaps, should be taxonomically divided into subspecies. The older form from Novoukrainka differs from the typical form Stegotetrabelodan (Tetralophodon) grandincisivus in some primitive peculiarities of the structure. The mentioned mastodon group is of interest from the view point of correlation of deposits containing their remains as well as of phyllogeny of the Proboscidea forms younger in the geological respect.